Portrait of International Backpacker Tourism during the COVID-19 Pandemic in Bali - WIRAWAN, Putu Eka; SUDJANA, I Made; SEMARA, I Made Trisna; ARIANTY, A.A Ayu Arun Suwi; NURUDDIN, NURUDDIN (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).03, 2021)
The world pandemic due to COVID -19 has destroyed almost all aspects of human life in the world, including the tourism sector. However, the existence of backpacker tourists is unique, because they can still contribute to local communities in Kuta Bali. This study aims to determine the impact of COVID -19 on the level of backpacker tourist visits in Bali and see the benefits generated by backpacker tourists during the pandemic. The entire research and writing process was designed using a qualitative method with a case study approach through in-depth interviews with several random tourists. The results of this study indicate that the pandemic due to COVID -19 has had an impact on the decline in the number of backpacker tourists in Bali. However, they can still contribute to the local community's economy during a pandemic.